Discovery and identification of a series of alkyl decalin isomers in petroleum geological samples1. Issue 13 (7th July 2015) - Wang, Huitong; Zhang, Shuichang; Weng, Na; Zhang, Bin; Zhu, Guangyou; Liu, Lingyan
<x xml:space="preserve">Abstract</x> A series of pairwise alkyl-decahydronaphthalene isomers were identified in petroleum geological samples by GC × GC/TOFMS.